Pengaruh Sistem Pengendalian Intern Pemerintah dan Moralitas Individu pada Kesalahan Akuntansi - Dennyningrat, I Gusti Agung Gde; Suputra, I D.G. Dharma (E-Jurnal Akuntansi; Vol 22 No 2 (2018), 2018)
Accounting mistakes are a mistake in financial facts. In order for an agency or company does not occur accounting errors, agencies or companies need to consider the factors that affect accounting errors. The purpose of this study is to provide empirical evidence of the effect of Government Internal Control System and individual morality on accounting errors. This research was conducted at Local Government of Badung Regency. Population in this research is all financial officer at Badung Regency Government. The number of samples taken as many as 35 employees, with purposive sampling technique. The data were collected by questionnaire method. Data analysis technique used is multiple linear regression analysis. Based on the results of the analysis, it is known that the Government Internal Control System and individual morality have a negative effect on accounting errors in Badung District Government. Keywords: internal control system, individual morality, accounting error